Mechanisms of Human Innate Immune Evasion by Toxoplasma gondii - Lima, Tatiane S.; Lodoen, Melissa B. (Frontiers in Cellular and Infection Microbiology, 2019)
Toxoplasma gondii is an intracellular protozoan parasite of global importance that can remarkably infect, survive, and replicate in nearly all mammalian cells. Notably, 110 years after its discovery, Toxoplasmosis is still a neglected parasitic infection. Although most human infections with T. gondii are mild or asymptomatic, T. gondii infection can result in life-threatening disease in immunocompromised individuals and in the developing fetus due to congenital infection, underscoring the role of the host immune system in controlling the parasite. Recent evidence indicates that T. gondii elicits a robust innate immune response during infection. Interestingly, however, T. gondii has evolved strategies to successfully bypass or manipulate the immune system and establish a life-long infection in infected hosts. In particular, T. gondii manipulates host immunity through the control of host gene transcription and dysregulation of signaling pathways that result in modulation of cell adhesion and migration, secretion of immunoregulatory cytokines, production of microbicidal molecules, and apoptosis. Many of these host-pathogens interactions are governed by parasite effector proteins secreted from the apical secretory organelles, including the rhoptries and dense granules. Here, we review recent findings on mechanisms by which T. gondii evades host innate immunity, with a focus on parasite evasion of the human innate immune system.